Frontline Demonstrations: An approach for management of chilli thrips (Scirtothrips dorsalis Hood) (Indian Journal of Arid Horticulture, 2016)
Front line demonstrations were conducted to popularize the recommended practice for the management of chillithrips in Panchmahals district of central Gujarat. Results indicated that application of insecticide in recommended practices,i.e., ethion 40 % + cypermethrin 5 % @ 0.045 % was found most effective in managing chilli thrips (1.07/leaf) as comparedto farmers practices (3.09/leaf). The yield of chilli in recommended practice was 128.13 q/ha as compared to farmer'spractices (80.30 q/ha). The percentage increased in the yield over farmer's practices was computed to be 59.56. Results ofstudy on economic analysis of the yield performance revealed that the recommended practices recorded appreciable highergross returns (10,2500/ha) and net return C 61,725/ha) with higher benefit cost ratio (2.51) as compared to farmer's practices(1.62). The technology gap (21.87 q/ha), extension gap (47.83 q/ha) and the technology index values (14.58 %) wererecorded. Frontline demonstrations brought out that the recommended practice was feasible and economically viable overfarmers practice and was a better option to adopt for managing chilli thrips.
Keywords: Frontline demonstrations; insecticide; Scirtothrips dorsalis; chilli